2020
DOI: 10.1080/21645515.2020.1726680
|View full text |Cite
|
Sign up to set email alerts
|

Co-presence of Epstein–Barr virus and high-risk human papillomaviruses in Syrian colorectal cancer samples

Abstract: We recently performed two studies exploring the presence of Epstein-Barr virus (EBV) and high-risk human papillomaviruses (HPVs) types 16, 18, 31, 33 and 35 in human colorectal cancers from the Syrian population. Herein, we report that EBV and high-risk HPVs are co-present in colorectal cancers from Syria. We reveal that 17 (~17%) of 102 cancer samples are positive for both EBV and high-risk HPVs and their copresence is associated with high/intermediate grade invasive carcinomas. These data suggest that EBV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 35 publications
13
37
0
Order By: Relevance
“…Polymerase chain reaction (PCR) technique was employed by most of the studies [ 8 , 10 , 11 , 13 , 17 - 35 , 37 – 49 , 52 , 54 , 55 , 57 91 ] to detect the presence of HPV in the normal, adjacent/benign and diseased samples using L1, E6 and E7 gene-specific primers which specifically target [ 6 , 11 , 16 , 18 , 31 , 33 , 35 , 39 , 40 , 42 , 45 , 51 59 ] the subtypes of HPV, and from them, in addition, few studies also employed the second techniques including immunohistochemistry [ 67 ] and Southern blotting [ 13 , 28 ] to validate their PCR results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymerase chain reaction (PCR) technique was employed by most of the studies [ 8 , 10 , 11 , 13 , 17 - 35 , 37 – 49 , 52 , 54 , 55 , 57 91 ] to detect the presence of HPV in the normal, adjacent/benign and diseased samples using L1, E6 and E7 gene-specific primers which specifically target [ 6 , 11 , 16 , 18 , 31 , 33 , 35 , 39 , 40 , 42 , 45 , 51 59 ] the subtypes of HPV, and from them, in addition, few studies also employed the second techniques including immunohistochemistry [ 67 ] and Southern blotting [ 13 , 28 ] to validate their PCR results.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies also used immunohistochemistry [ 31 , 36 , 51 , 56 ], gene chip technology [ 53 ], Southern blotting [ 50 ] and in situ hybridisation [ 12 ] for the detection of HPV, and they did not validate their results through any other technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumors were considered positive for E6 and LMP1 if cancer cells exhibited positivity ≥1% of the cells [ 69 ]. In the case of LMP1 protein expression, we also evaluated the presence of viral infection in tumor-infiltrating lymphocytes and stromal cells [ 69 , 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been reported that the co-occurrence of high-risk HPVs and EBV in oral cancer is associated with a significant increase in the invasiveness ability of cancer cells ( 25 ). We recently demonstrated that the co-presence of high-risk HPVs and EBV is linked to high/intermediate grade in different types of human carcinomas including HN ( 5 , 26 , 27 ). Thus, it is evident that the co-presence of high-risk HPVs and EBV in high-grade human carcinomas could suggest a possible cooperation between their oncoproteins; however, there are only few studies regarding the co-presence of high-risk HPVs and EBV in the ME region focusing only on NPCs.…”
Section: Introductionmentioning
confidence: 99%